Attitudes of Teachers and Students towards the Possibilities of GIS Implementation in Secondary Schools in Croatia - Silvija Šiljeg; Antonio Milanović; Ivan Marić (MDPI AG, 2022)
The geographic information system (GIS) is, at the global level, recognized as one of the best ICTs for implementation in the subject of geography. The application of GIS in the Republic of Croatia (RH) lags behind developed countries. The main objective of this research was to examine the attitudes of secondary school students and geography teachers regarding the introduction of GIS in the educational system process. In the period from 3 October 2021 to 27 January 2022, a survey questionnaire was conducted in 30 secondary schools in the RH on a sample of 611 students and 96 teachers. The results have showed that both teachers and students have a positive attitude toward the introduction of GIS for the purpose of teaching geography. More than 80% of teachers believe that GIS is not sufficiently represented in the high school and geography curricula which is recognized as one of the most important factors which limit GIS implementation. A majority (77%) of teachers are not using GIS on any teaching level, which is not surprising since both surveyed teachers and students have poor knowledge of GIS, although teachers rated their knowledge a little higher. Teachers perceive students' interest in GIS exactly as students express it; predominantly indifferent. The most important factors limiting the implementation of GIS are recognized as: a lack of necessary GIS software and licenses; not knowing how to use GIS; and an insufficient number of teaching units dedicated to GIS in the geography curricula. An equal percentage of both teachers and students believe that there are prerequisites for GIS implementation in their schools. One of the basic prerequisites for GIS implementation is that education authorities need to "see" GIS as an important part of geography and include it more in school curricula. In almost all countries where GIS has been implemented in schools, difficulties in its implementation have been documented.